The Comparison of Effectiveness between Bee Venom and Sweet Bee Venom Therapy on Low back pain with Radiating pain - Lee Tae-ho; Hwang Hee-sang; Chang So-young; Cha Jung-ho; Jung Ki-hoon; Lee Eun-young; Roh Jeongdu (Korean Pharmacopuncture Institute, 2007)
Objective : The aim of this study is to investigate if Sweet Bee Venom therapy has the equal effect in comparison with Bee Venom Therapy on Low back pain with Radiation pain. Methods : Clinical studies were done 24 patients who were treated low back pain with radiation pain to Dept. of Acupuncture & Moxibusition, of Oriental Medicine Se-Myung University from April 1, 2007 to September 30, 2007. Subjects were randomly divided into two groups ; Bee Venom treated group(Group A, n=10), Sweet Bee Venom treatred group(Group B, n=14). In Bee Venom treated group(Group A), we treated patients with dry needle acupuncture and Bee Venom therapy. In Sweet Bee Venom treatred group(Group B), we treated patients with dry needle acupuncture and Sweet Bee Venom therapy. All process of treatment were performed by double blinding method. To estimate the efficacy of controlling pain. we checked Visual Analog Scale(VAS). For evaluating functional change of patients, Straight Leg Raising Test(S.L.R.T) was measured. Results :1. In controlling pain, Sweet Bee Venom treatred group(Group B) had similar ability in comparison with Bee Venom treated group(Group A). 2. In promoting function, Sweet Bee Venom treatred group(Group B) had similar ability in comparison with Bee Venom treated group(Group A). Conclusions : It may be equal effects as compared with using Bee Venom to treat low back pain with radiation pain using Sweet Bee Venom. We can try to treat other disease known to have effect with Bee Venom.